Políticas públicas para radiodifusão e imprensa: ação e omissão do estado no Brasil pós-1964 - Pieranti, Octavio Penna (2005)
The press and the State had developed, in Brazil, a relation of interdependence. Press and broadcasting corporations depend on state money for its survival and politicians depend on the press and the exposition in the media to communicate with their electorate. This relation of proximity affects the elaboration of public policies for the sector. This study analyzes public policies for broadcasting and the press since 1964, when it was established in the country the military regimen, a mark of a deep reform in the Communications. Public policies are debated in line with two dimensions - one relative to the infrastructure needed by the Communications, and another referring to the content of information. Our conclusion clarifies the urgency of a revision in the laws that regulate the media, many of which are not applicable anymore, and questions the independence of Brazilian parliamentarians to proceed with the necessary reforms and to the discussion about new public policies for the sector.